Superior Organizational Culture Improves Performance at PT. Kereta Api Indonesia (Persero) - Mufida, Alfriana Zahru; Sari, Rita Irma; Wahjono, Sentot Imam (Golden Ratio of Data in Summary, 2025)
Organizational culture plays a vital role in shaping organizational members' beliefs, attitudes, and behaviors. Its influence can be seen through team member performance, which reflects their attitude towards the company. Good performance not only benefits the company but also benefits the employees themselves. This study explores the organizational culture's influence on employee performance at PT Kereta Api Indonesia (Persero). The method used in this research is qualitative with a descriptive approach. Data collection was conducted through library research, which involved analyzing relevant literature, such as papers, books, and other writings related to the problem under study. From the analysis conducted, it was found that the organizational culture at PT Kereta Api Indonesia (Persero) was excellent. In addition, the company's performance has also shown excellent results. Thus, it can be concluded that organizational culture positively and significantly influences employee performance at PT Kereta Api Indonesia (Persero).